Ferramenta para identificação de potenciais parcerias entre unidades agroindustriais na geração de biogás - Souza, Jovani Taveira de (2022)
One of the major obstacles to the development of projects and businesses involving biogas in most countries, despite its numerous benefits, is the lack of collaborative partnerships between biomass producers. Although these producers generate waste with high energy potential for biogas production, this potential ends up being wasted. In addition, many of them do not want to invest in the installation of biodigesters, as they consider these values to be too high. Thus, it is often unfeasible for small rural producers to install their own biodigesters due to the high costs and also the low volume of waste they generate, thus not compensating for such installation. In this scenario, a solution to provide collaborative opportunities for the generation of biogas is through a tool that helps in the establishment of collaborative partnerships between these producers to take advantage of the combined resources, allocating them to the production of biogas. Therefore, the objective of this thesis was to develop a Web tool, called BCluster, based on the clustering process, with the objective of identifying potential partnerships between agro-industrial units for the generation of biogas, considering aspects such as: geographic location, distance between units, potential for biogas production, proximity to the gas pipeline network, proximity to the main energy consumers, among others. Multicriteria methods were used to assist in the decision-making process regarding the choice of the most adequate number of clusters. The tool was applied in two cases, considering different scenarios for cluster calculation. The results showed that the tool allows decision makers to identify the location of the units and centralizing units of each cluster, differentiated by color; identify the total biogas potential of each cluster; identify the distance between the units of a cluster and its respective centralizing unit; and also knowing the route and distance between the units and centralizing units. In addition, the developed tool provides organized, reliable, comprehensive and flexible information, with a view to the territorial development of a given region, offering the possibility for producers to organize themselves into associations to properly dispose of the waste produced on their respective properties, thus minimizing the possible environmental impacts resulting from the activity and, at the same time, generating new business opportunities and thus increasing the competitiveness of the agro-industrial sector.